Settlement of Land Plot Location Disputes Through Mediation: Case at Kediri Regency Land Office - Rahmalia Pawestri; Isdian Anggraeny; Dwi Ratna Indri Hapsari (Universitas Muhammadiyah Malang, 2024)
A dispute over the location of a land plot is a dispute caused by confusion in the designation of land plots or boundaries. This dispute can cause losses for parties who have an interest in the land plot. Land dispute resolution, one of which is a dispute over the location of land parcels, can be resolved through non-litigation channels through mediation. Mediation as an alternative to dispute resolution is considered more profitable for the parties because it uses a win-win solution method. This research is an empirical juridical research, using primary and secondary data sources. The location of the research is at the Kediri Regency Land Office. The result of this study is the implementation of mediation at the Kediri Regency Land Office through several stages guided by Article 6 paragraph (1) of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning the Handling and Settlement of Land Cases. The implementation of mediation at the Kediri District Land Office has obstacles including the parties to the dispute not being present at the time of mediation and having a bad faith. In this case, the solution that can be provided by the Kediri District Land Office is to advise the parties to resolve the dispute through litigation at the Kediri District District Court. Abstrak Sengketa letak bidang tanah merupakan sengketa yang disebabkan oleh kekeliruan dalam penunjukan bidang atau batas tanah. Sengketa ini dapat menyebabkan kerugian bagi pihak yang memiliki kepentingan atas bidang tanah tersebut. Penyelesaian sengketa pertanahan salah satunya sengketa letak bidang tanah dapat diselesaikan melalui jalur non litigasi melalui mediasi. Mediasi sebagai alternative penyelesaian sengketa dinilai lebih menguntungkan bagi para pihak sebab menggunakan metode win-win solution. Penelitian ini merupakan penelitian yuridis empiris, dengan menggunakan sumber data primer dan sekunder. Lokasi penelitian berada di Kantor Pertanahan Kabupaten Kediri. Hasil penelitian ini adalah pelaksanaan mediasi di Kantor Pertanahan Kabupaten Kediri melalui beberapa tahapan yang berpedoman pada Pasal 6 ayat (1) Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 21 tahun 2020 tentang Penanganan dan penyelesaian Kasus Pertanahan. Pelaksanaan mediasi di Kantor Pertanahan Kabupaten Kediri memiliki hambatan diantaranya adalah para pihak yang bersengketa tidak hadir pada saat mediasi serta beritikad tidak. Dalam hal ini, solusi yang dapat diberikan oleh pihak Kantor Pertanahan Kabupaten Kediri adalah menyarankan kepada para pihak untuk menyelesaikan sengketa melalui jalur litigasi di Pengadilan Negeri Kabupaten Kediri.